Serum haptoglobin correlates positively with cholesterol and triglyceride concentrations in an obese Mongolian population - Soejima, Mikiko; Munkhtulga, Lkhagvasuren; Furukawa, Kyoji; Iwamoto, Sadahiko; Koda, Yoshiro (Clinica chimica acta, 2020)
•Polymorphisms of HP associated with serum HP but not with cholesterol levels.•Association of HP polymorphisms with serum HP level was weakened in obese subjects.•Positive correlations between serum HP and cholesterol or TG levels were observed.•Degree of obesity affects the relationships between serum HP and lipid levels. Recent studies revealed that several genetic polymorphisms of haptoglobin gene (HP) and the haptoglobin-related protein gene (HPR) associated not only with haptoglobin (HP) but total, non-HDL, and/or LDL cholesterol concentrations in various populations. Association between serum HP concentrations and polymorphisms of HP and the HPR gene, or anthropometric and metabolic factors were examined in Mongolian participants (n = 927) using linear regression analyses. The association of HP and HPR polymorphisms with serum HP concentration but not serum lipids concentrations was observed. However, subgroup analysis revealed that the association of HP and HPR polymorphisms with serum HP concentration was weakened in subgroup of obese (BMI ≥ 30) subjects and positive correlations between serum HP and non-HDL cholesterol, HDL cholesterol or triglyceride concentrations were observed in the obese subjects as compared with in subgroups of normal weight (BMI < 25) and overweight (25 ≤ BMI < 30) subjects. The degree of obesity strongly affects the relationships between serum HP concentrations and several genetic, anthropometric and metabolic factors. These results suggested that we need to take into account the degree of obesity when considering the HP polymorphisms as predictive markers for clinical states.